RATIONING OF METAL – CHARGE COMPONENTS, APPLIED IN STEEL SMELTING, IN THE SAP R/3 SYSTEM - N. P. Papkov (Литьë и металлургия)
The program, presented in this article enables to use fully the developed methodosgy for the calculation of metal-burden components consumрtion norms, thus reducing the effort required to conduct analytical work and improve the efficiency of the analysis results in management decisions